Hypercube emulation of interconnection networks topologies. (4th January 2016) - Alahmadi, Adel; Alhazmi, Husain; Ali, Shakir; Deza, Michel; Sikirić, Mathieu Dutour; Solé, Patrick
Abstract : We address various topologies (de Bruijn, chordal ring, generalized Petersen, and meshes) in various ways (isometric embedding, embedding up to scale, and embedding up to a distance) in a hypercube or a half‐hypercube. Example of obtained embeddings: infinite series of hypercube embeddable bubble sort and double chordal rings topologies, as well as of regular maps. Copyright © 2016 John Wiley & Sons, Ltd.